Thermo‐Responsive Structure and Surface Activity of Kinetically Stabilized Micelle Composed of Fluorinated Alternating Peptides in Organic Solvent. Issue 16 (24th April 2018) - Ihsan, Abu Bin; Koyama, Yasuhito; Taira, Toshiaki; Imura, Tomohiro
Abstract: Three‐component polycondensation with an aldehyde, perfluoroalkylammonium triflate, and potassium isocyanoacetate produced amphiphilic fluorinated alternating peptides. The polymers work as a surfactant, which form associates in organic solvent. The thermo‐dependent structures and surface activity of the associates in organic solvents were evaluated by the results of UV‐vis and diffusion‐ordered NMR spectral measurements at various concentrations and temperatures. It also turned out that the regularly aligned bulky substituents in the main chain stabilize the micelles kinetically formed in organic solvent. Abstract : Three‐component polycondensation with an aldehyde, perfluoroalkylammonium triflate, and potassium isocyanoacetate produced amphiphilic fluorinated alternating peptides. The polymers work as a surfactant, which form associates in organic solvent. The biphenyl substituents of the polymer are perfectly aligned neighboring to the perfluoroalkyl groups as an organophobe. The regularly aligned bulky substituents in the polypeptide main chain strongly contribute on the kinetic stability of micelles.